Study of the Inhibitory Action of Marboran on the Replication Cycle of Cowpox Virus (Res Medica, 2014)
Research ProjectThe project undertaken involved a study of the effects of the inhibitor N-methyl isatin thiosemicarbazone (Marboran) on the replication cycle of cowpox virus in monolayers of baby hamster kidney cells (BHK).The cytotoxic effects of Marboran on the BHK cells were studied and were found to be directly related to the time of exposure to the inhibitor with a maximum tolerated dose of Marboran of 30/UM/ml. after 7 days. This drug concentration was subsequently used to avoid the occurrence of a cytotoxic effect of Marboran masking any cytopathic effect (CPE) of the virus when both inhibitor and virus were used in conjunction.